2021
DOI: 10.1177/20503121211016156
|View full text |Cite
|
Sign up to set email alerts
|

Wealth index and other behavioral and sociodemographic characteristics associated with body mass index in Ethiopia

Abstract: Background: Nowadays, the burden of non-communicable diseases including obesity has been an increasing public health concern. This menace can be monitored using indexing method like body mass index. Studies indicate that socioeconomic indicators such as income, biology, behavior, and demographic factors associated with body mass index. In Ethiopia, few studies associate wealth index with body mass index in people of ages between 15 and 49. This study was aimed to assess the association of body mass index with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…This contributes to adverse effects on the child as well as maternal health [5]. Among numerous short birth intervals, adverse effects on child stunting, underweight and wasting [16,17] are the most common despite it is also substantially associated with the household wealth index [18]. Place of delivery and residence, age of mothers at first birth, mother's current marital status, mothers and husband/partner education level, region, religion, household size, household wealth index, and child mortality was independently associated with recurrent birth events.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to adverse effects on the child as well as maternal health [5]. Among numerous short birth intervals, adverse effects on child stunting, underweight and wasting [16,17] are the most common despite it is also substantially associated with the household wealth index [18]. Place of delivery and residence, age of mothers at first birth, mother's current marital status, mothers and husband/partner education level, region, religion, household size, household wealth index, and child mortality was independently associated with recurrent birth events.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies ( 3 , 10 , 11 ) demonstrated factors, mainly wealth index, contributing to malnutrition among under-five children and have been stable to date in developing countries in particular. However, the contribution of the wealth index to malnutrition may be mediated by other socioeconomic, demographic, behavioral, and biological factors despite little attention being given.…”
Section: Introductionmentioning
confidence: 99%
“…Breast feeding and mothers age at first birth have also a significant effect on underweight and wasting respectively. The lower wealth index of the household highly associated with higher risk of underweight and wasting among under five children as it is also supported in [ 7 ].…”
Section: Discussionmentioning
confidence: 73%
“…Based on 2018 WHO global reports, the prevalence of anthropometric indicators stunting, underweight and wasting in under five children were 24.7%, 15.1%, and 7.8%, respectively [ 6 , 7 ]. Even if these problems are common all over the world, it is most dominant in low and middle income countries like Ethiopia.…”
Section: Introductionmentioning
confidence: 99%